2006
DOI: 10.1021/jm058289o
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Subsite Binding to the β5 Subunit of the Human 20S Proteasome Using Vinyl Sulfones and 2-Keto-1,3,4-oxadiazoles:  Syntheses and Cellular Properties of Potent, Selective Proteasome Inhibitors

Abstract: Beginning with the peptide sequence Cbz-Ile-Glu(OtBu)-Ala-Leu found in PSI (3), a series of vinyl sulfones (VS) were synthesized for evaluation as inhibitors of the chymotrypsin-like activity of the 20S proteasome. Variations at the key P3 position confirmed the importance of a long side chain capped with a hydrophobic group for optimal potency, consistent with a model of binding to the S3 subsite. The tert-butyl glutamic ester initially used at P3 gave plasma unstable, insoluble compounds and was replaced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Although the calculated model did not show any interaction between the substituent at P2 position and residues of proteasome, the authors found that a bulky group at this position would prevent water molecules from attacking the covalent inhibitor and thus it would stabilize the complex and improve the activity. This theoretical result was consistent with the results of a series of peptide-like vinyl sulfones [80].…”
Section: Covalent Dockingsupporting
confidence: 91%
“…Although the calculated model did not show any interaction between the substituent at P2 position and residues of proteasome, the authors found that a bulky group at this position would prevent water molecules from attacking the covalent inhibitor and thus it would stabilize the complex and improve the activity. This theoretical result was consistent with the results of a series of peptide-like vinyl sulfones [80].…”
Section: Covalent Dockingsupporting
confidence: 91%
“…Monosubstituted oxadiazoles are deprotonated at the ring carbon atom to give the corresponding anion, which has been subsequently alkylated with various alkylating agents. Thus, for example, 2-substituted-1,3,4-oxadiazoles 959 after treatment with butyllithium in the presence of MgBr 2 diethyl etherate in THF, [613,614].…”
Section: Reactions Of Substituentsmentioning
confidence: 99%
“…Various natural and synthetic compounds that contain electrophilic centres or ‘warheads’ inhibit the proteasome by forming covalent adducts with these active-site threonine residues, including peptide aldehydes, vinyl sulfones, boronic acids, α′β′-epoxyketones, 2-keto-1,3,4-oxadiazoles and β-lactones (Figure 1A) [46,911]. The di-peptide boronic acid bortezomib (PS-341 or VELCADE®, Millennium Pharmaceuticals, Inc.) is among the most potent, stable and selective of these inhibitors [1215], and shows nanomolar potency with respect to cytotoxicity across a broad range of human tumour cell types in vitro [13,14].…”
Section: Introductionmentioning
confidence: 99%